Social Assessment and the El Salvador Basic Education Modernization Project - World Bank (Washington, DC, 2012)
The World Bank supports development that improves human welfare and reduces poverty. Achieving this goal requires sustainable economic growth; the development of physical infrastructure, human resources, and institutions; and sound environmental management. In recent years development practitioners have recognized that having stakeholders participate in project selection and design has a number of advantages: it can help reach the poor and other vulnerable groups, strengthen participants' "ownership" of the project, and improve decision-making. Development practitioners also recognize that systematic social analysis can help ensure that projects achieve their objectives, that they are appropriately targeted, that they are acceptable to the intended beneficiaries, and that they are institutionally feasible. Social assessment (SA) supports participation, and is a tool for incorporating social analysis into the Bank's projects and analytical work.